(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The aim of the research is to identify the impact of credit shocks on the market value of banks, and data were collected on the research sample represented by the (Iraqi Investment Bank) for the period (2010-2020) and a simple regression model was used as well as extracting the value (R²) to explain the effect of the independent variable on the changes that occur On the dependent variable, as well as the standard coefficient of regression (b), which measures the response of the dependent variable when the independent variable changes by one standard degree, using the statistical program (SPSS), and the research reached a set of practical results, including that there is a significant effect relationship between credit shocks and value The market for the bank is at a level of significance of (0.05), and the researchers suggested a number of recommendations, including the need for attention by the management of banks to study credit shocks and indicate the extent of their impact on other banking indicators. Which affects the financial position of the banks, which negatively affects the market value of its shares.